Pengembangan Sistem Informasi Kurban Pada Proses Pendukung dan Pendaftaran Kurban (Studi Kasus: Masjid Ibnu Sina Kota Malang) - Fikri Hernanda; Ismiarta Aknuranda; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Ibnu Sina Mosque is one of the mosques located in Malang that has functions like a mosque in general. The mosque has one of its functions, namely the social function to prosper the surrounding community. One of the social activities and is one of the worship of Muslims is to carry out sacrifice activities that are held every year. The organization of the activities of takmir and remaja of Ibnu Sina Mosque formed a committee to carry out the sacrifice activities. However, there are some problems that occur in the process of performing sacrifices. In the supporting process, namely the recording of preparatory data, sacrifices, equipment, slaughter team, and recipients of the sacrifices, it is often difficult to trace the data in the previous year and it is prone to disappear. Based on these problems, this study aims to build a sacrificial information system that can help the process of supporting and the main process of sacrifice in managing the list of sacrifices, recipients of sacrifices, slaughterers, equipment, and list of sacrificial animals. The construction of this system uses Laravel framework to facilitate development by applying the principle of object orientation. This system development method uses an iterative model approach. Then the system is tested using the validation and the compatibility testing. The validation test demonstrates that the system is valid and the compatibility test result shows the system has a good compatibility score on all web browsers.